Control of stereoselectivity in 4-tert-butylphenol hydrogenation over a carbon-supported rhodium catalyst by carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Ebina, Takeo; Shirai, Masayuki (Chemistry Letters, 2006)
cis-4-tert-Butylcyclohexanol was obtained with a high cis ratio (cis/(cis + trans) = 0.9) in the hydrogenation of 4-tert-butylphenol over a carbon-supported rhodium catalyst along with hydrochloric acid in supercritical carbon dioxide solvent.

Low temperature hydrogenation of tetralin over supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Shirai, Masayuki (Applied Catalysis A-General, 2006)
Hydrogenation of tetralin was studied over supported rhodium catalysts in supercritical carbon dioxide solvent at 333 K. The results were compared with those in an organic solvent and under neat conditions. Higher cis-decalin yield was obtained in supercritical carbon dioxide solvent than under non-supercritical conditions. It was observed that higher hydrogen concentration at the surface in supercritical carbon dioxide solvent led to fast direct hydrogenation of tetralin to cis-decalin; the flipping of the intermediate, octalin, to give trans-decalin could be prevented. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cis-decalin; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide; supported rhodium catalysts; tetralin

Selective hydrogenation of naphthols to tetralones over supported palladium catalysts in supercritical carbon dioxide solvent - Mine, Eiichi; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2006)
Naphthols were selectively hydrogenated to the corresponding tetralones over supported palladium metal catalysts in super-critical carbon dioxide solvent.

Stereoselective hydrogenation of tert-butylphenols over charcoal-supported rhodium catalyst in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, Chandrashekhar V.; Sato, Osamu; Tetsuka, Hiroyuki; Shirai, Masayuki (Journal of Catalysis, 2007)
Hydrogenation of 2-, 3-, and 4-tert-butylphenols was studied over a charcoal- supported rhodium catalyst in supercritical carbon dioxide (scCO(2)) solvent, and the results were compared with those in organic solvents. In the hydrogenation of 4-tert-butylphenol, a higher cis ratio for 4-tert-butylcyclohexanol (0.79) was obtained in scCO(2) (10 MPa) than in 2-propanol (0.70) and cyclohexane (0.64) under similar conditions of hydrogen pressure (2 MPa) and temperature (313 K). In the case of 2-tert-butylphenol, the cis ratio for 2-tert-butylcyclohexanol was as high as 0.95 in both scCO(2) and 2-propanol (hydrogen pressure, 2 MPa; reaction temperature, 313 K). In the case of hydrogenation of 3-tert-butylphenol, the cis ratio decreased with the progression of consecutive hydrogenation of 3-tert-butylcyclohexanone intermediate. In addition, the stereoselectivity to cis-tert-butylcyclohexanols in scCO(2) was improved in the presence of hydrochloric acid. It was found that the protons of hydrochloric acid accelerated the hydrogenation of the intermediates, tert-butylcyclohexanones, to the corresponding cis-tert-butylcyclohexanols. The hydrogenation mechanism of tert-butylphenols, particularly the enhanced selectivity to cis-tert-butylcyclohexanols in scCO(2), is postulated based on the observed reaction profiles. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: charcoal-supported rhodium catalyst; stereoselective hydrogenation; supercritical carbon dioxide solvent; tert-butylcyclohexanol

Enhancement of glycerol conversion to acetol in high-temperature liquid water by high-pressure carbon dioxide - Yamaguchi, Aritomo; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2008)
Dehydration of glycerol to acetol proceeded in high-temperature liquid water at 573 K in a batch reactor. The acetol formation rate increased with an addition of high-pressure carbon dioxide.

Phase behavior of hydrogenation of 2-tert-butylphenol over a charcoal-supported rhodium catalyst in carbon dioxide solvent - Hiyoshi, Norihito; Masuda, Yoshio; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of Chemical and Engineering Data, 2009)
Catalytic hydrogenation of 2-tert-butyl phenol over a charcoal-supported rhodium catalyst in carbon dioxide solvent at 313 K was studied in a batch reactor. To elucidate the effect of carbon dioxide pressure on the initial rate of reaction, the phase behavior of the ternary (2-tert-butylphenol-carbon dioxide-hydrogen) system was separately observed with a view cell, and the calculations of vapor-liquid equilibrium and compositions in the vapor and liquid phases inside the reactor were carried out using the Peng-Robinson equation of state. The hydrogenation behavior in the carbon dioxide solvent is discussed based on the phase behavior of the ternary system.

Kinetic analysis of 4-isopropylphenol hydrogenation over activated carbon-supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Green Chemistry, 2012)
Hydrogenation behavior of 4-isopropylphenol to 4-isopropylcyclohexanol over activated carbon-supported rhodium catalysts in supercritical carbon dioxide (scCO(2)) at 313 K was studied in a batch reactor and the results were compared with those in 2-propanol. Higher yields of cis-4-isopropylcyclohexanol were obtained in scCO(2) than in 2-propanol, and the formation of a byproduct, isopropylcyclohexane, was suppressed in scCO(2). The catalyst modification with hydrochloric or phosphoric acid enhanced the yield of cis-4-isopropylcyclohexanol in both scCO(2) and 2-propanol solvents. Kinetic analyses of the reaction profiles revealed higher reaction rates in scCO(2) than those in 2-propanol for the 4-isopropylcyclohexanol formation both by the direct hydrogenation of 4-isopropylphenol and by the consecutive hydrogenation of 4-isopropylcyclohexanone, and also revealed that the addition of hydrochloric acid increased the consecutive hydrogenation rate of 4-isopropylcyclohexanone to cis-4-isopropylcyclohexanol, which reduced the total reaction time needed for the complete hydrogenation of 4-isopropylphenol to 4-isopropylcyclohexanol.

Effect of carbon dioxide pressure on 4-t-butylphenol hydrogenation activity of supported rhodium catalyst - Hiyoshi, Norihito; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of the Japan Petroleum Institute, 2013)
Hydrogenation of 4-t-butylphenol over an activated carbon-supported rhodium catalyst in carbon dioxide solvent was analyzed based on phase observation with a view cell and calculations of the solubility of 4-t-butylphenol using the Peng-Robinson equation of state as a function of carbon dioxide pressure. The reaction experiments showed that the initial reaction rate of 4-t-butylphenol at 313 K under 2 MPa of hydrogen pressure was increased by the addition of carbon dioxide, especially above a total pressure of 11 MPa. Direct visual observation showed that the solubility of 4-t-butylphenol increased with higher carbon dioxide pressure. The calculations based on the Peng-Robinson equation of state also showed that the solubility of 4-t-butylphenol in the 4-t-butylphenol carbon dioxide hydrogen (2 MPa) system at 313 K significantly increased by addition of carbon dioxide above a total pressure of 11 MPa. We concluded that the increase in the hydrogenation rates was caused by the increased concentration of 4-t-butylphenol substrate in the carbon dioxide solvent.
Keywords: 4-t-Butylphenol hydrogenation; Carbon dioxide solvent; Peng-Robinson equation; Rhodium catalyst; Supercritical fluid

Hydrogenolysis of benzofuran using aqueous ethanol solution over graphite-supported platinum catalyst - Hiraishi, Yushi; Minakawa, Naohiro; Taniguchi, Kenkichi; Nagasawa, Yoshiyuki; Nanao, Hidetaka; Rode, V, Chandrashekhar; Sato, Osamu; Yamaguchi, Aritomo; Shirai, Masayuki (Journal of the Indian Chemical Society, 2021)
Graphite-supported platinum catalysts (Pt/G) were highly active for the hydrogenolysis of benzofuran to o-ethylphenol in aqueous ethanol solution at 523 K without using any external hydrogen gas. The hydrogenolysis activities and selectivity to o-ethylphenol in ethanol solution over Pt/G were higher than those with a conventional method using externally supplied hydrogen gas. Both water and ethanol were indispensable for the hydrogenolysis in aqueous ethanol solution at 523 K.
Keywords: Biomass conversion; Graphite support; Hydrogenolysis; platinum catalysts

Conversion of benzyl phenyl ether to monoaromatics in high-temperature aqueous ethanol solution under high-pressure carbon dioxide conditions - Taniguchi, Kenkichi; Kusumawati, Etty N.; Nanao, Hidetaka; Rode, Chandrashekhar V.; Sato, Osamu; Yamaguchi, Aritomo; Shirai, Masayuki (New Journal of Chemistry, 2023)
Solvolysis of benzyl phenyl ether (BPE), which is a model compound of lignin ether linkage, was studied in an aqueous ethanol solution, which can be obtained from bioethanol, under high-pressure carbon dioxide conditions. A batch study revealed that BPE solvolysis to monoaromatics (benzyl ethyl ether (BEE), benzyl alcohol (BA), and phenol (Ph)) proceeded in aqueous ethanol solution over 523 K and the addition of high-pressure carbon dioxide enhanced the initial solvolysis rate and suppressed the side reaction (hydrogenolysis to toluene (TL)). The ethanol molar fraction (ethanol-water volume ratio) is the key factor for the solvolysis reaction, and the highest monoaromatic yield of 72.9% (BEE 10.7%, BA 19.3%, Ph 37.9%, and TL 5.1%) was obtained in aqueous ethanol solution (2 cm(3) : 1 cm(3) = water:ethanol) at 598 K for 3 h under a pressure of 18 MPa of carbon dioxide. The solvolysis reaction proceeded continuously to produce monoaromatics with a flow system. A monoaromatic yield of 76.7% (BEE 8.6%, BA 19.7%, Ph 39.6%, and TL 8.9%) was obtained, and the formation rates were 2.7 x 10(-4) mmol min(-1) for BEE, 6.2 x 10(-4) mmol min(-1) for BA, and 12.4 x 10(-4) mmol min(-1) for Ph at 598 K under flowing water (26 mmol min(-1)), ethanol solution (4.1 mmol min(-1)), carbon dioxide (1.2 mmol min(-1)), and BPE (15.6 x 10(-4) mmol min(-1)) under a total pressure of 40 MPa.